Structural Equation Model for BIM Adoption in the Turkish Construction Industry - Aladag, Hande; Demirdogen, Gokhan; Demirbag, Alperen Taha; Isik, Zeynep (TURKISH CHAMBER CIVIL ENGINEERS, 2026)
The construction industry is criticized as lagging behind other sectors in terms of digitalization and technology adoption. Building Information Modelling (BIM) is widely acknowledged as a transformative tool that can drive significant progress in the construction industry amid ongoing technological developments. Despite widespread recognition of BIM's benefits for the construction industry, adoption rates in T & uuml;rkiye remain below expectations. Therefore, this study aims to present a BIM adoption model tailored to the Turkish construction industry. The model was tested using the Structural Equation Modelling (SEM) method, incorporating insights from 150 industry professionals in T & uuml;rkiye. According to the SEM analysis results, Environmental Factors have a significant impact on Organizational Factors and Perceived Ease of Use while Behavioral Intention mediates the relationship between Perceived Usefulness and Actual BIM Usage. Developed model highlights key areas for BIM adoption improvement in T & uuml;rkiye. Additionally, the model can serve as a tool for assessing BIM adoption performance and facilitating benchmarking between companies, thereby boosting overall industrial success through improved BIM adoption.
Keywords: Building Information Modelling (BIM); construction industry; digitalization; Structural Equation Modelling (SEM); technology adoption; ACCEPTANCE; TECHNOLOGY; IMPLEMENTATION; ANTECEDENTS; PERCEPTIONS; READINESS; Engineering